The Effect Of Combination Spherical Grip And Kinesio Taping Exercise To Enhance Of Muscle Strength In Ischemic Stroke Patients In Jemursari Islamic Hospital Surabaya - Qori Mariyanto; Handa yani; Wesiana Herisanti (Alma Ata University Press, 2018)
Ischemic stroke patients are the main problem that occurs when disruption of cerebral blood flow. Data Global Burden Disease shows that all populations obtained 80% ischemic stroke and 20% hemorrhagic stroke with physical mobility barriers namely muscle weakness obtained 58%. Nursing actions that can be done, one of which is by giving activity to stroke patients who are useful to increase cerebral blood flow. This study aims to analyze the effect of the combination of spherical grip exercise and Kinesiotaping to the muscle strength of ischemic stroke patients in Jemursari Islamic Hospital Surabaya.This research is designed by Quasi Experiment with approach pre post test control group design. All populations are ischemic stroke patients in the azzahra room 1 as many as 41 people, a sample of 38 respondents divided into 19 treatment and control groups. In the intervention group was given a combination of Spherical Grip and Kinesiotaping Exercise for 20 minutes twice a day for 3 weeks. Whereas in the control group was given training accordance with Hospital procedures. Statistical analysis used Wilcoxon signed rank test and Mann-Whitneyα test< 0,05.The results of this study indicated that the mean increase in muscle constriction in the intervention group 2.83, and a big control group is 1.10. Analysis with Mann Whitney showed p= 0.000. So that H0 rejected this means that there is an effect of a combination of Spherical Grip and Kinesiotaping exercises on increasing muscle strength in ischemic stroke patients in Jemursari Islamic hospitals.The combination of Spherical Grip and Kinesiotaping exercises that are routinely performed can increase muscle strength, resulting in increased muscle strength in ischemic stroke patients. Nurses need to apply Spherical Grips and Kinesiotaping to ischemic stroke patients in the rehabilitation phase. Keyword : Ischemic stroke, Spherical Grip and Kinesiotaping, Muscle Strength.